(untitled) (CIPEEX, 2025)
International experience offers multiple opportunities for the development of fundamental skills and competencies in a global context. This study explores the influence of a stay in Italy on the author’s academic and professional development, focusing on the acquisition of competencies such as intercultural communication, adaptability, and problem-solving in a multicultural environment. Through a qualitative approach, based on literature review and documented accounts, the positive impacts of cultural immersion on strengthening a global mindset and expanding professional networking are analyzed. The results indicate that international experience is a relevant driver for professional growth, highlighting the role of intercultural interactions and new perspectives gained in diverse contexts, essential in a globalized labor market.